Designing Digital Reading Materials Based on Bantenese Local Wisdom for EFL Undergraduate Students - Imam Fauzi; Sholeh Hidayat; Yudi Juniardi; Wahyudin Wahyudin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research study investigated the local wisdom and culture of Banten implemented in the digital reading materials design. The research objectives are creating the reading materials using Flip PDF Professional software that rely on the local wisdom of Banten. Research design used is research and development (R&D) in this study. The second semester undergraduate students of Faculty of Social and Political Science, Universitas Serang Raya are the subject of this research study. Research data is obtained through validation form, questionnaire, and test. To analyze the research data used the descriptive analysis with SPSS 21. The results of the investigation, the digital reading materials design based on local wisdom using Flip PDF Pro that was developed can positively engage the EFL students in the language learning, and the reading texts effectively give social and cultural values with 83,75% the average of content feasibility and 80% the average of reading materials presentation. Additionally, the value of Sig. (2- tailed) was 0,00 < α (α = 0,05) as it is proven that the students’ reading ability is getting better and the digital reading materials that is designed was feasible and can be utilized by the EFL students and teachers in their English Foreign Language classroom activities.